Valorizing Shrimp Shell as a Source of Chitin with Crude Enzymes from Germinated Winter Wheat and Buckwheat - Ng, Ying; Khor, Jing Wei; Chang, Ying Ping (Food Science and Engineering, 2023)
Chitin is a valuable resource found in shrimp shells. Typically, the industrial process for isolating chitin from crustacean shells involves using chemical methods that require large amounts of acid and alkaline. While commercial protease application is a more environmentally friendly method, it can be costly. Germinated grains can be a source of low-cost protease for chitin isolation. This study aimed to assess the effectiveness of crude enzymes extracted from germinated winter wheat (Triticum aestivum) and buckwheat (Fagopyrum esculentum) to isolate crude chitin from white shrimp shells. The proteolytic and chitinolytic activities of the crude enzyme extracts were determined and applied in the deproteinization step during chitin isolation from shrimp shells. The deproteinization rate was assessed, the crude chitin yield was compared, and the isolated chitins were characterized through Fourier Transform Infrared (FTIR) spectroscopy analysis and x-ray diffraction (XRD) analysis. Crude enzymes extracted from germinated winter wheat and buckwheat exhibited proteolytic activity of approximately 0.49 U/mL and 0.46 U/mL, respectively. Using winter wheat extract and buckwheat extract acted on demineralized shrimp shells exerted a deproteinization rate of 53.6 ± 1.0% and 58.0 ± 2.3% and yielded 30.3 ± 5.31% and 29.2 ± 3.99% crude chitin, respectively. FTIR spectra of the isolated chitins showed amide I, amide II, amide III, asymmetric stretching of the C-O-C bridge, O-H stretching, N-H stretching and asymmetric C-H stretching, typical functional groups for chitin. The crystallinity index for commercial chitin, chemical-isolated chitin, winter wheat extract-isolated chitin and buckwheat extract-isolated chitin was 86.49%, 88.74%, 88.82% and 75.87%, respectively. Buckwheat extract-isolated chitin, deacetylated with lower crystallinity, warrants further investigation. Crude enzymes from winter wheat and buckwheat to remove protein from demineralized shrimp shells can be a more environmentally friendly method to valorize shrimp shells as a chitin source.